Ambiguitas dan Distorsi Makna dalam Al-Qur’an - Ummu Salamah; Ira Ainul Latifah; Mauidlotun Nisa; Wati Susiawati (Institut Muslim Cendekia, 2025)
This research discusses the ambiguity and distortion of meaning contained in letters in the Al-Qur'an. In semantic studies, ambiguity or unclear meaning can be caused by several things, including words that have general characteristics or sentences that are never one hundred percent homogeneous. Meanwhile, distortion occurs due to a lack of knowledge or action on the part of each individual who wants to understand the verse according to his wishes and wants to stimulate other people to deviate from understanding the meaning of the verse of the Qur'an. By using the literature review method, the researchers tried to collect material systematically about the ambiguity and distortion of meaning contained in several verses of the Qur'an from previous studies. In this research, the researchers describe examples of ambiguity and distortion of meaning in the Qur'an. There is ambiguity in the meaning of surah al-Baqarah verse 228 and an-Nisa verse 43 from Kamaluddin Abunawas' research, surah al-Baqarah verse 223 and an-Nisa verse 34 in Iswah Adriana's research, surah al-Baqarah verse 220 in Salman et al.'s research. And there is a distortion of meaning in surah al-Baqarah verses 191 and 255 from Septiani et al.'s research, surah Thaha verse 121, an-Nisa verse 164, al-A'raf verse 179 from AN's Nirvana research. And in this research the researchers also try to provide an attitude towards facing ambiguity and distortion of meaning in the verses of the Qur'an.